Evaluasi Penggunaan Obat Triheksifenidil sebagai Terapi Adjuvan pada Pasien Skizofrenia di Instalasi Rawat Inap Rumah Sakit Jiwa Daerah Sungai Bangkong Pontianak - Musdalifah, Wiranti; Susanti, Ressi; ., Robiyanto (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Schizophrenia is a chronic and severe mental disorder that affects how a person thinks, feels, and behaves. The main therapy for schizophrenia is anti-psychotic medication. A variety of side effects arise from the use of antipsychotic drugs including extrapyramidal syndrome. Trihexyphenidyl is an anticholinergic drug which is commonly use in preventing and treating extrapyramidal symptoms caused by antipsychotic. This study aims to know the patterns of trihexyphenidyl usage and rationality of trihexyphenidyl usage in Inpatient Installation of Sungai Bangkong Psychiatric Hospital Pontianak. The method of this study was a observational method with descriptive cross sectional study design. Data were taken from patients medical record by purposive sampling technique. Samples in this study were 165 patients. Based on results, combination therapy of the most widely prescribed was trihexyphenidyl with risperidone - clozapine - trifluoperazine (35,76%). Trihexyphenidyl dose of the most widely prescribed was 2 x 2 mg/day (93,94%). Antidepressants were the most commonly used class of drugs (38,64%). Percentage of appropriate indication, appropriate drug, appropriate dose, appropriate route, appropriate frequency of administration and beware of the side effects of drugs in the use of trihexyphenidyl were respectively 64,25%, 100%, 100%, 100%, 100%, and 100%. Based on the results of study there are 109 patients (64,25%) that comply all of the medication rationality criteria.